Analysis of Debt Value to Negative Equity at PT Garuda Indonesia (Persero) Tbk - Setiawan, Agus; Bahiyyah, Khariidatul; Fitriani, Rani Ligar (Jurnal Wacana Ekonomi, 2024)
This research aims to analyze the effect of debt value on negative equity at PT Garuda Indonesia (Persero) Tbk. Hypothesis testing is carried out using the t statistical test. The sampling technique used is nonprobability sampling with data taken from the second quarter of 2020 to the third quarter of 2023, when negative equity occurs. The results of the analysis show that the value of debt has a negative effect on negative equity. The new finding in this research is that companies took 25 months to gradually recover from the Covid-19 pandemic. A high debt value causes negative equity, the company obtains more capital from debt because business activity is low. It would be better for companies to increase business activities by increasing flight schedules for profitable routes.